Methodologies to represent and promote the geoheritage using unmanned aerial vehicles, multimedia technologies, and augmented reality - Santos, Ivaneide (2018)
Promoting geoheritage using the Internet materializes mainly through the use of maps, posters, informational murals, or websites. This information is usually detailed and visually appealing. However, in most cases, there is little interactivity and a limited or complete lack of contextualization within the geographical space. The main objective of this work was to integrate information collected with unmanned aerial vehicles, georeferenced information processed in geographical information systems, photogram- metry techniques, and multimedia technologies to promote a better computer visualization of geoheritage. A working website was built based on panoramic photography, three-dimensional representation of the terrain, and multimedia information, in order to provide a pleasant way of promoting and interacting with field geology by using the Internet. The navigation through the information is based on 360° spherical panoramic images that are fully oriented and georeferenced. Their movement can be perfectly synchronized with the viewing of the landscape by using motion sensors found on portable devices (tablets or smartphones) such as GPS, accelerometers, gyroscopes, or compasses. These images can include the access to multimedia elements such as websites, videos, images, sounds, interpretation models, text, or interactive 3D terrain models, working as an excellent support base for the provision of an augmented reality experience. If used in the field, this technical implementation can act as an interactive guide for the interpretation of the landscape. This type of content can be accessed online from locations with a network signal or can be obtained in advance for offline use.